Pelatihan Pemberdayaan Zakat Berbasis Masjid untuk Peningkatan Ekonomi Masyarakat di Kota Gorontalo - Ivan Rahmat Santoso (Jurnal Pengabdian Pada Masyarakat, 2020)
MOSQUE-BASED ZAKAT EMPOWERMENT TRAINING TO IMPROVE COMMUNITY ECONOMY IN GORONTALO CITY. The empowerment of Zakat applied so far has been focused more on zakat which is consumptive and sometimes lacks the target and is effective for the recipient of zakat. The purpose of this dedication activity is to optimize the empowerment of zakat which is more productive in a mosque-based manner. The implementation method used is a combination of socialization and training. The results obtained from this training are knowledge about community economic empowerment by using zakat instruments for the community and more specifically mosque management which includes the formation of zakat collection units, administrative management and effective distribution of zakat for zakat mustahik.